2005
DOI: 10.1143/jjap.44.5866
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fast-Photospeed Chemically Amplified Resist in Extreme Ultraviolet Lithography

Abstract: In a high-annealing type resist system that employs polyhyodroxy styrene as a base resin, we found that tri-phenysulfonium cyclo(1,3-perfluoropropanedisulfone) imidate when employed as a photoacid generator (PAG) is more sensitive than tri-phenysulfonium nonaflate under extreme ultraviolet (EUV) exposure. However, their sensitivities are almost the same under KrF and EB exposures. As results of both outgassing species and FT-IR measurements, the EUV-induced reaction of cyclo(1,3-perfluoropropanedisulfone) imid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Table 4 shows the total outgassing displacement before and after EUV exposure calculated using the computation method described in our previously published paper. 8 The amount of outgassing from polymers A and B were found to be the same as for ref. (MAdM).…”
Section: -2 Outgassing Of Chalcogen Atom-including Polymer Resists Umentioning
confidence: 62%
See 1 more Smart Citation
“…Table 4 shows the total outgassing displacement before and after EUV exposure calculated using the computation method described in our previously published paper. 8 The amount of outgassing from polymers A and B were found to be the same as for ref. (MAdM).…”
Section: -2 Outgassing Of Chalcogen Atom-including Polymer Resists Umentioning
confidence: 62%
“…6 On the other side, it is reported that the sensitivity tendencies in EB and EUV exposures are not same, and to achieve high sensitivity direct excitation reaction have to add in the acid generation mechanism in EUV. 8 In this study, we evaluated the sensitivity of several polymers that include chalcogen atoms (i.e., oxygen or sulfur) for EUV exposure. Additionally, we measured outgassing from these polymers under EUV exposure.…”
Section: Introductionmentioning
confidence: 99%
“…As the content of PAG is small in general, for the analysis of the reaction mechanism of the PAG in the resist films, other analysis method such as Fourier-transform infrared spectroscopy (FT-IR) is very difficult [26][27][28]. Since the synchrotron light has strong light intensity, the TEY method using this light is more effective.…”
Section: Soft X-ray Absorption Spectroscopymentioning
confidence: 99%
“…Furthermore, the absorption peak at 287 eV corresponds to the -bonding of the protection group of tert-butylacrylate (TBA) of the base polymer. From the outgassing results [25][26][27][28][29] , this changes correspond only to the protecting group decomposition reaction of TBA in base polymer occurred by the secondary electron originated by the EUV irradiation as shown in Fig. 7.…”
Section: Sr Absorption Spectroscopymentioning
confidence: 99%
“…In the previous report, for resists which employed tri-phenylsulfonium cyclo(1,3-perfluoropropanedisulfone) imidate (TPS-Imidate-1) and tri-phenylsulfonium perfluorobutane-sulfonate (TPS-Nonaflate) as PAGs, the peak at the absorbance at 1156 cm -1 in the fourier transform infrared (FT-IR) spectra increased after EUV exposure. [25][26][27][28][29] As a results of the electron orbital calculation using perturbation theory by the software code Gaussion03 30) , the peak at approximately 1156 cm -1 in FT-IR spectra of resist A corresponds to the C-F bonding of the anion of TPS-Imidate-1. However, there was no change in the FT-IR spectra of resist which include TPS-Nonaflate, between before and after EUV exposure.…”
Section: Introductionmentioning
confidence: 99%